1999
DOI: 10.1002/(sici)1521-4141(199906)29:06<1890::aid-immu1890>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate protects mice from lethal shock induced by LPS or TNF-α

Abstract: Although important advances have been made in the development of antibiotics and medical intensive care technology in recent years, systemic response to infection remains a major health problem, with growing incidence and high mortality rates. Here we demonstrate the ability of the antioxidant agent pyrrolidine dithiocarbamate (PDTC) to inhibit the in vivo activation of NF-O B in lung and liver tissues, as well as the systemic release of TNF- § in lipopolysaccharide (LPS)-treated mice. The in vivo effect of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 44 publications
(48 reference statements)
5
30
0
Order By: Relevance
“…26 PDTC is another effective free radical scavenger. In vivo, PDTC protected mice from endotoxin and tumor necrosis factor a-induced lethal shock, 27,28 rabbits from staphylococcal enterotoxin A-induced fever 29 and cold perfusion-induced injury to orthotopic rat liver transplants. 30 In vitro, it has been reported to reduce the effect of ultraviolet radiation in experiments with cultured cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…26 PDTC is another effective free radical scavenger. In vivo, PDTC protected mice from endotoxin and tumor necrosis factor a-induced lethal shock, 27,28 rabbits from staphylococcal enterotoxin A-induced fever 29 and cold perfusion-induced injury to orthotopic rat liver transplants. 30 In vitro, it has been reported to reduce the effect of ultraviolet radiation in experiments with cultured cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, LPS stimulation results in rapid release of TNF-␣ and IL-1␤, whereas release of IL-10 is delayed (5). In the past, LPS-activated monocytes have been manipulated through the use of ␤-agonists (42), antioxidants (43), and adenosine receptor agonists (44,45), resulting in reduced production of proinflammatory cytokines and augmented IL-10 production. We have shown that contact with apoptotic neutrophils has a similar quantitative effect (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6). Furthermore, administration of PDTC, a well characterized inhibitor of NF-B activation and TNF-␣ production (37), to mice prior to treatment with LPS did not alter the change in MTP1 expression induced by LPS (data not shown).…”
Section: Figmentioning
confidence: 92%